Modifying plants for biofuel and biomaterial production. Issue 9 (December 2014) - Furtado, Agnelo; Lupoi, Jason S.; Hoang, Nam V.; Healey, Adam; Singh, Seema; Simmons, Blake A.; Henry, Robert J.
Summary The productivity of plants as biofuel or biomaterial crops is established by both the yield of plant biomass per unit area of land and the efficiency of conversion of the biomass to biofuel. Higher yielding biofuel crops with increased conversion efficiencies allow production on a smaller land footprint minimizing competition with agriculture for food production and biodiversity conservation. Plants have traditionally been domesticated for food, fibre and feed applications. However, utilization for biofuels may require the breeding of novel phenotypes, or new species entirely. Genomics approaches support genetic selection strategies to deliver significant genetic improvement of plants as sources of biomass for biofuel manufacture. Genetic modification of plants provides a further range of options for improving the composition of biomass and for plant modifications to assist the fabrication of biofuels. The relative carbohydrate and lignin content influences the deconstruction of plant cell walls to biofuels. Key options for facilitating the deconstruction leading to higher monomeric sugar release from plants include increasing cellulose content, reducing cellulose crystallinity, and/or altering the amount or composition of noncellulosic polysaccharides or lignin. Modification of chemical linkages within and between these biomass components may improve the ease of deconstruction. Expression of enzymes in the plant may provide a cost‐effective option for biochemical conversion to biofuel.